Junge Szene Wien '89. - Amanshauser, Hildegund (Wien : Wiener Secession, 1989)
Baumgartner, Michael ; Bressnik, Heiko ; Bressnik, Uwe ; Dapunt, Irene ; Dertnig, Carola ; Moos, Pia ; Durstmüller, Harald ; Erjautz, Manfred ; Höck, Richard ; Hoffmann, Guido ; Hohenbüchler, Christine ; Hohenbüchler, Irene ; Kersten, Thomas ; Kos, Michael ; etc.
Junge Szene Wien '89, Wiener Secession, Wien, 26. Juli bis 27. August 1989
Duits
kunstcatalogus
Keywords: Wenen